Comparison of Static Model, Adaptation Study, and CFD Simulation in Evaluating Thermal Comfort Based on Köppen Climate Classification System in Churches in Indonesia - Cornelia Hildegardis; Anak Agung Ayu Oka Saraswati; I Dewa Gede Agung Diasana Putra; Ni Ketut Agusinta Dewi (Journal of Engineering and Technological Sciences, 2021)
This research examined thermal comfort in  church buildings in Indonesia by making a comparison between three different Indonesian climatic regions using three different research models. A static model, an adaptation study model and a CFD simulation were used to find the similarities and differences between the results generated from determining thermal comfort in church buildings in the three regions. The comparison revealed that church buildings had different PMV scores at each measuring point that were inversely proportional to the subjects’ response on thermal comfort inside the buildings, i.e. points adjoining with openings affect a low PMV score and a high perceived thermal sensation, and vice versa. The CFD simulation showed that changing the conditions of the openings affects air velocity and flow into the building, which influences the subjects’ thermal comfort response inside the churches.